2008
DOI: 10.1590/s1516-14392008000400012
|View full text |Cite
|
Sign up to set email alerts
|

Properties of SBS and sisal fiber composites: ecological material for shoe manufacturing

Abstract: The worldwide trend toward using cheap, atoxic and durable materials from renewable resources contributes to sustainable development. Thus, the investigation of the potential use of vegetal fibers as reinforcing agent in polymeric composites has gained new significance. Sisal fiber has emerged as a reinforcing material for polymers used in automobile, footwear and civil industries. In this work, properties such as hardness, tensile strength and tear strength of polymer composites composed by block copolymer st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…The second step is due to the cellulose decomposition which produces a relatively high char residue. 25,26 Only one degradation step was observed for the neat polymer and for the composites, and the thermal stability was better for the composites but did not change significantly with increasing fibre content. The surrounding polymer seems to have protected the fibre from lower-temperature degradation, and the interaction between the fibre and the polymer seems to have retarded the degradation process and/or restricted the diffusion of volatile degradation products out of the sample.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…The second step is due to the cellulose decomposition which produces a relatively high char residue. 25,26 Only one degradation step was observed for the neat polymer and for the composites, and the thermal stability was better for the composites but did not change significantly with increasing fibre content. The surrounding polymer seems to have protected the fibre from lower-temperature degradation, and the interaction between the fibre and the polymer seems to have retarded the degradation process and/or restricted the diffusion of volatile degradation products out of the sample.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…The later degradation can be ascribed to the breaking of polyethylene segment present in EVA and degradation of butadiene present in SBS polymer. [ 41,42 ] No significant variation found in DTG curve due to incorporation of LDPE in blends (both A and C samples).…”
Section: Resultsmentioning
confidence: 96%
“…Many authors reported that decomposition of EVA proceeds at about 300°C by the elimination of vinyl acetate via chain scissoring [ 38–40 ] and SBS start decomposing above 350°C. [ 41,42 ]…”
Section: Resultsmentioning
confidence: 99%
“…A degradação das fibras de curauá começa em cerca de 250°C, assim a temperatura de processamento em 150°C provavelmente não afeta a estabilidade térmica do composto (VERNEY;LIMA;LENZ, 2008). Foram utilizados tratamentos químicos tais como a mercerização nas fibras e o polipropileno enxertado com anidrido maleico (MA-g-PP) como agente de acoplamento na preparação dos compósitos, o que promoveu a maior adesão interfacial entre as fibras e a matriz, de modo que o desempenho mecânico dos compósitos resultantes pode ser melhorado.…”
Section: O Processamentounclassified